Two EM-type channel estimation algorithms for OFDM with transmitter diversity. - Yongzhe Xie (IEEE Transactions on communications)
We study channel estimation for orthogonal frequency-division multiplexing (OFDM) systems utilizing transmitter diversity and operating over multipath fading channels. Two expectation-maximization (EM)-type algorithms are introduced and compared with each other in terms of convergence rate. At each iteration and for every OFDM link, the EM-type algorithms partition the problem of estimating a multi-input channel into independent channel estimations for each transmit-receive antenna pair, therefore avoiding the matrix inversion encountered in the joint least-square estimation. The EM-type algorithms can also be used to efficiently implement a recently proposed algorithm, termed the significant-tap-catching estimator, so that the system performance is more robust to different multipath channel delay profiles.